Pretrial Home Detention with Electronic Monitoring: An Evaluation in Marion County, Indiana, 1988-1989 - Maxfield, Michael G. ([Verlag nicht ermittelbar], 1992)
For this data collection a pretrial home detention program in Marion County, Indiana, that relied on electronic monitoring of clients was subjected to a nonexperimental evaluation. The data address whether the pretrial electronic monitoring program was effective in ensuring that clients appeared at their court hearings, whether the pretrial electronic monitoring program was effective in ensuring public safety, and the extent to which field contact officers experienced difficulties in attempting to contact clients. To gauge the success of the program, investigators compared the number of successful terminations (i.e., home detention followed by a court appearance) to the number of unsuccessful terminations (technical violations and absconding). Each client in the pretrial program was fitted with a coded wristlet that matched a base unit receptacle. A successful contact between the coded wristlet and the base unit verified the client's presence. Defendants on home detention were monitored by a field contact officer. Variables in this collection include charged offense, prior criminal history, living arrangements, employment status, number of telephone calls, summary of program violations, reason for program termination, program entry and termination dates, and disposition after program release. The unit of observation is the individual program client.